Efficacy of pediatric integrative manual therapy in positional plagiocephaly: a randomized controlled trial - Iñaki Pastor-Pons; María Orosia Lucha-López; Marta Barrau-Lalmolda; Iñaki Rodes-Pastor; Ángel Luis Rodríguez-Fernández; César Hidalgo-García; Jose Miguel Tricás-Moreno (BMC, 2021)
Abstract Background Positional plagiocephaly frequently affects healthy babies. It is hypothesized that manual therapy tailored to pediatrics is more effective in improving plagiocephalic cranial asymmetry than just repositioning and sensory and motor stimulation. Methods Thirty-four neurologically healthy subjects aged less than 28 weeks old with a difference of at least 5 mm between cranial diagonal diameters were randomly distributed into 2 groups. For 10 weeks, the pediatric integrative manual therapy (PIMT) group received manual therapy plus a caregiver education program, while the controls received the same education program exclusively. Cranial shape was evaluated using anthropometry; cranial index (CI) and cranial vault asymmetry index (CVAI) were calculated. Parental perception of change was assessed using a visual analogue scale (− 10 cm to + 10 cm). Results CVAI presented a greater decrease in PIMT group: 3.72 ± 1.40% compared with 0.34 ± 1.72% in the control group (p = 0.000). CI did not present significant differences between groups. Manual therapy led to a more positive parental perception of cranial changes (manual therapy: 6.66 ± 2.07 cm; control: 4.25 ± 2.31 cm; p = 0.004). Conclusion Manual therapy plus a caregiver education program improved CVAI and led to parental satisfaction more effectively than solely a caregiver education program. Trial registration Trial registration number: NCT03659032 ; registration date: September 1, 2018. Retrospectively registered.